Ion- And Photon- Induced Mass Spectrometry of Natural Products: Ion Formation, Matrix Effects and Instrumentation - Coorey, R.V. (Faculty of Science, University of Colombo, 2001)
Ionization pathways and matrix-effects in plasma desorption (PD) and laser desorption (LD) time-of-flight (TOF) mass spectrometry (MS) of low-mass (0.1-1.0 kDa) natural products (alkaloids and compounds that are present in spicy plants) have been studied in this thesis. The PD-TOF-MS results of natural products suggest that most of the target specific fragment ions are formed via uni-molecular dissociation of M1-* and Mtf ions probably in the selvedge (gas) phase. The low-mass (i.e. less than m/z 70) positive ions, formed under PD conditions are found to be mostly unspecific in nature. These ions could originate either from the hot core of the infra-track or from the surrounding area of the track and the ‘entropic breakup model’ best describes the formation of these ions. In contrast, a universal hydrocarbon negative ion series independent of the target compound is observed for negative ions and the ‘adiabatic expansion model’ best describes the formation of these ions. Probable explosive matrix-assistance in PD-TOF-MS, via the explosive energy flow through explosive decomposition under the action of 252Cf fission fragment impact, has been demonstrated using a matrix (HMX)/analyte (insulin) as a model. Probable intermediate products that result from explosive decomposition (e.g. NO, NO2, HNO2, HCN), which are in highly vibrationally excited states are assumed to transfer their “excess” vibrational energy to analyte (e.g. proteins) molecules for their efficient desorption/ionization. Furthermore, an enhanced protonation of the analyte is explained through collisions with chemically decomposed products of explosives and due to their electron scavenging effect. The LD-TOF-MS results of natural products indicate dominant ion-molecular reactions in the laser plume (i.e. in the gas phase). However, in matrix-assisted laser desorption/ionization (MALDI) conditions, ion-molecular reactions are considerably reduced. The ionization step is likely to take place at the very early stages of the development of the MALDI plume, where the cxcitcd-state matrix molecules are likely to act as precursors to produce protonated analyte species via matrix to analyte proton transfer mechanism. Different mass spectrometric techniques such as PD, delayed extraction-MALDI and electrospray ionization (ESI) coupled to either TOF with an electrostatic ion reflector or Fourier transform ion cyclotron resonance mass analyzer with MS/MS are used to detect, isolate and characterize the individual components present in a mixture of alkaloids and curcuminoids in a curcumin sample. Thesis also describes the construction details and preliminary results of the performance of a MALD1-TOF mass spectrometer that has been constructed at the Department of Physics, University of Colombo for the first time. As the initial results, the protonated molecular ions of try8-bradykinin (1077.2 Da) and N-acetyl renin substrate